Arte contemporânea e experiências: um diálogo com professoras de educação infantil e ensino fundamental - Ferreira, Adriana Maria do Nascimento (2012)
This task s purpose was to discuss the experiences of four female teachers, being teacher 1 a pedagogue of child education, teachers 2 and 3 pedagogues of initial years and teacher 4 a bachelor in art education. Monthly meetings were used to promote a dialog with their experiences and with contemporary art. It was a qualitative study, through the Education Cultural Studies theoretical-methodological approach. This research results from the need to think a formative process which may address contemporary questions about art and education. A conclusion is that despite their lack of profound experiences with contemporary art, there are inquietudes which lead to glimpses of such experience, allowing, then, discussions about it.